2017
DOI: 10.1186/s13561-017-0157-3
|View full text |Cite
|
Sign up to set email alerts
|

Economic conditions, hypertension, and cardiovascular disease: analysis of the Icelandic economic collapse

Abstract: Previous research has found a positive short-term relationship between the 2008 collapse and hypertension in Icelandic males. With Iceland's economy experiencing a phase of economic recovery, an opportunity to pursue a longer-term analysis of the collapse has emerged. Using data from a nationally representative sample, fixed-effect estimations and mediation analyses were performed to explore the relationship between the Icelandic economic collapse in 2008 and the longer-term impact on hypertension and cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Those include changes in personal income, health behaviors, and individual labor-market status (Asgeirsdottir et al, 2016a;Asgeirsdottir et al, 2014a;Asgeirsdottir et al, 2016b;Asgeirsdottir et al, 2014b;Birgisdottir et al, 2017;Jonsdottir & Asgeirsdottir, 2014;Miller et al, 2009;Olafsdottir & Asgeirsdottir, 2015;Olafsdottir et al, 2014;Ruhm, 2000Ruhm, , 2003Ruhm, , 2007Ruhm, , 2015. Miller et al (2009) found that the added deaths related to a drop in the unemployment rate are concentrated among age groups that are mostly out of the labor force, indicating that work-related stress or substitution between work and health production are not primarily to blame.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those include changes in personal income, health behaviors, and individual labor-market status (Asgeirsdottir et al, 2016a;Asgeirsdottir et al, 2014a;Asgeirsdottir et al, 2016b;Asgeirsdottir et al, 2014b;Birgisdottir et al, 2017;Jonsdottir & Asgeirsdottir, 2014;Miller et al, 2009;Olafsdottir & Asgeirsdottir, 2015;Olafsdottir et al, 2014;Ruhm, 2000Ruhm, , 2003Ruhm, , 2007Ruhm, , 2015. Miller et al (2009) found that the added deaths related to a drop in the unemployment rate are concentrated among age groups that are mostly out of the labor force, indicating that work-related stress or substitution between work and health production are not primarily to blame.…”
Section: Introductionmentioning
confidence: 99%
“…The health outcomes previously explored include a number of determinants of cardiovascular diseases (CVD) (Asgeirsdottir et al (2016a); Asgeirsdottir et al (2014a); Asgeirsdottir et al (2016b); Asgeirsdottir et al (2014b); Birgisdottir et al (2017); (Eiriksdottir et al, 2015); Hauksdottir et al (2013); Jonsdottir and Asgeirsdottir (2014); McClure et al (2012); Olafsdottir and Asgeirsdottir (2015); Olafsdottir et al (2014)). Using survey data from , Asgeirsdottir et al (2014b find a short-term increased risk of male hypertension following the economic collapse and with an added wave of the same data for 2012, Birgisdottir et al (2017) also show a longer-run rise in hypertension among females, and Eiriksdottir et al (2015) find an increased risk of gestational hypertension after the economic collapse. Furthermore, data from the emergency departments in Iceland's capital area indicate a considerable increase in cardiac emergency department attendance during the first week of the economic collapse, particularly among females, and particularly with IHD diagnoses (Gudjonsdottir et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Economic prosperity of communities have created new health problems of metabolic concern such as the hyperuricemia and systemic hypertension. 1 Both are related to each other through weight gain and increased metabolic process. In developing countries, the use of meat increases the body weight and is related to the increased uric acid levels in the blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic hypertension has become a major public health problem in the urban communities of developing countries. 1,2 Systemic hypertension is a risk for morbid health owing to increased risk of myocardial infarction, cardiac failure, renal failure, cerebrovascular disorders, and the peripheral arterial disease (PAD). 1 Estimates shows the total world burden of subjects suffering from systemic hypertension approximates to 1 billion people and 7.1 million deaths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation